THE INFLUENCE OF JOB STRESS AND PERSON-ORGANIZATION FIT ON TURNOVER INTENTION BY USING JOB SATISFACTION AS MEDIATING ROLE - Lupiana, Feri; Rijanti, TRistiana (Proceeding SENDI_U, 2015)
This research investigates the influence of job stress, person-organization fit onturnover intention by using job satisfaction as mediating role, study in PT. HerculonCarpet. The study is mainly based on review of the existing literature and collection ofdata through an adopted questionnaire survey, conducted from the selected sample of PT.Herculon Carpet. A total of 212 questionnaires were distributed among the sample whichis selected using the technique of purposive sampling. 176 respondents returned thequestionnaire, which are utilized for the analysis purpose. The result found that jobstress positively influences job satisfaction, person-organization fit positivelyinfluences job satisfaction, while job stress positively influences turnover intention,person-organization fit negatively and non significantly influences turnover intention,job satisfaction positively influences turnover intention and job satisfaction mediates jobsatisfaction on turnover intention. This research is limited by other independent variablewhich are not investigated in this research, therefore the R square value is only 0.400.Key words: Job Stress, Person-Organization Fit, Job Satisfaction, TurnoverIntention